Origin, evolution and genome distribution of microsatellites - Oliveira,Eder Jorge (2006)
Microsatellites, or simple sequence repeats (SSRs), have been the most widely applied class of molecular markers used in genetic studies, with applications in many fields of genetics including genetic conservation, population genetics, molecular breeding, and paternity testing. This range of applications is due to the fact that microsatellite markers are co-dominant and multi-allelic, are highly reproducible, have high-resolution and are based on the polymerase chain reaction (PCR). When first introduced, the development of microsatellite markers was expensive but now new and efficient methods of repetitive sequence isolation have been reported, which have led to reduced costs and microsatellite-technology has been increasingly applied to several species, including non-model organisms. The advent of microsatellite markers revolutionized the use of molecular markers but the development of biometric methods for analyzing microsatellite data has not accompanied the progress in the application of these markers, with more effort being need to obtain information on the evolution of the repetitive sequences, which constitute microsatellites in order to formulate models that fit the characteristics of such markers. Our review describes the genetic nature of microsatellites, the mechanisms and models of mutation that control their evolution and aspects related to their genesis, distribution and transferability between taxa. The implications of the use of microsatellites as a tool for estimating genetic parameters are also discussed.